Focused Ultrasound-Induced Blood–Brain Barrier Opening to Enhance Temozolomide Delivery for Glioblastoma Treatment: A Preclinical Study - Wei, Kuo-Chen; Chu, Po-Chun; Wang, Hay-Yan Jack; Huang, Chiung-Yin; Chen, Pin-Yuan; Tsai, Hong-Chieh; Lu, Yu-Jen; Lee, Pei-Yun; Tseng, I-Chou; Feng, Li-Ying; Hsu, Peng-Wei; Yen, Tzu-Chen; et al. (PloS one, 2013)
The purpose of this study is to assess the preclinical therapeutic efficacy of magnetic resonance imaging (MRI)-monitored focused ultrasound (FUS)-induced blood-brain barrier (BBB) disruption to enhance Temozolomide (TMZ) delivery for improving Glioblastoma Multiforme (GBM) treatment. MRI-monitored FUS with microbubbles was used to transcranially disrupt the BBB in brains of Fisher rats implanted with 9L glioma cells. FUS-BBB opening was spectrophotometrically determined by leakage of dyes into the brain, and TMZ was quantitated in cerebrospinal fluid (CSF) and plasma by LC-MS\MS. The effects of treatment on tumor progression (by MRI), animal survival and brain tissue histology were investigated. Results demonstrated that FUS-BBB opening increased the local accumulation of dyes in brain parenchyma by 3.8-/2.1-fold in normal/tumor tissues. Compared to TMZ alone, combined FUS treatment increased the TMZ CSF/plasma ratio from 22.7% to 38.6%, reduced the 7-day tumor progression ratio from 24.03 to 5.06, and extended the median survival from 20 to 23 days. In conclusion, this study provided preclinical evidence that FUS BBB-opening increased the local concentration of TMZ to improve the control of tumor progression and animal survival, suggesting its clinical potential for improving current brain tumor treatment.